2015
DOI: 10.3126/jist.v19i2.13849
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mikania micrantha H.B.K. Invasion on Diversity and Abundance of Plant Species of Chitwan National Park, Nepal

Abstract: This research investigated the invasion of the alien plant Mikania micrantha H.B.K. and its impact on plant species richness and abundance in Chitwan National Park (CNP) forest. Stratified sampling technique was used to collect the information using the nested quadrats in the Mikania invaded and not invaded sites in July 2011. The study revealed that the invasion highly related with the vegetation structure of the habitat; higher the tree crown cover lower the invasion. On the other hand, the invasion in terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Murphy and other researchers found that Mikania micrantha is now found in 44% of his sampled habitats, with high infestation rates (50% coverage) in nearly 15% of these [17]. Highest densities were recorded in riverine forests, tall grasses and wetlands [18]. Species richness showed unimodel response to the Mikania cover percent with the decrease after 35% of Mikania cover.…”
Section: Disscussionmentioning
confidence: 76%
“…Murphy and other researchers found that Mikania micrantha is now found in 44% of his sampled habitats, with high infestation rates (50% coverage) in nearly 15% of these [17]. Highest densities were recorded in riverine forests, tall grasses and wetlands [18]. Species richness showed unimodel response to the Mikania cover percent with the decrease after 35% of Mikania cover.…”
Section: Disscussionmentioning
confidence: 76%
“…3). Negative effect of Mikania invasion on native species, biodiversity and livelihood of forest dependent community has been well studied in Chitwan National Park (Sapkota, 2007;Siwakoti, 2007;Ulak, 2010;Murphy et al, 2013;Rai & Scarborough, 2014;Shrestha & Dangol, 2015). This is the one of the study that reports the effect of Mikania invasion on regeneration condition of native tree species which shows that with the increase in 1 unit percentage of Mikania, there will be 0.504 units decrease in regeneration number of native forest species.…”
Section: Distribution Of Mikania Micranthamentioning
confidence: 93%
“…The invasion of non-native species is becoming one of the major threats for global biodiversity [1]. Compilation of a global dataset of regional first reports of alien species by [2] revealed that 37% of all first records of invasive species were reported within the period of 1970-2014.…”
Section: Introductionmentioning
confidence: 99%